Congress of Neurological Surgeons Systematic Review and Evidence-Based Guidelines for Perioperative Spine: Preoperative Pulmonary Evaluation and Optimization. (7th September 2021) - Mohamed, Basma; Wang, Marjorie C; Bisson, Erica F; Dimar, John; Harrop, James S; Hoh, Daniel J; Mummaneni, Praveen V; Dhall, Sanjay
Abstract: BACKGROUND: There are no current recommendations for preoperative pulmonary evaluation and management of patients undergoing elective spine surgery. OBJECTIVE: The aim of this guideline is to determine preoperative risk factors for perioperative and postoperative pulmonary adverse events and to determine the optimal preoperative evaluation and management of at-risk patients. METHODS: A systematic review of the literature was performed using the National Library of Medicine PubMed database and the Cochrane Library for studies relevant to postoperative pulmonary adverse events in patients undergoing spine surgery. Clinical studies evaluating preoperative patient risk factors and preoperative diagnostic and treatment interventions were selected for review. RESULTS: The literature search yielded 152 abstracts relevant to the PICO (patient/population, intervention, comparison, and outcomes) questions included in this chapter. The task force selected 65 articles for full-text review, and 24 were selected for inclusion in this systematic review. Twenty-three articles addressed preoperative patient risk factors. One article addressed preoperative diagnostic studies of pulmonary function. There were no studies meeting the inclusion criteria for preoperative pulmonary treatment. CONCLUSION: There is substantial evidence for multiple preoperative patient factors that predict an increased risk of a postoperative pulmonary adverse event. Individuals with these risk factors (functional dependence, advanced age [≥65 yr], chronic obstructive pulmonary disease, congestive heart failure, weight loss, and obstructive sleep apnea) who are undergoing spine surgery should be counseled regarding the potential increased risk of a perioperative and postoperative pulmonary adverse events. There is insufficient evidence to support any specific preoperative diagnostic test for predicting the risk of postoperative pulmonary adverse events or any treatment intervention that reduces risk. It is suggested, however, to consider appropriate preoperative pulmonary diagnostic testing and treatment to address active pulmonary symptoms of existing or suspected disease. The full guidelines can be accessed at https://www.cns.org/guidelines/browse-guidelines-detail/5-preoperative-pulmonary-evaluation-optimization .